Black pine (Pinus nigra) barks: A critical evaluation of some sampling and analysis parameters for mercury biomonitoring purposes. (May 2020) - Rimondi, Valentina; Costagliola, Pilario; Benesperi, Renato; Benvenuti, Marco; Beutel, Marc W.; Buccianti, Antonella; Chiarantini, Laura; Lattanzi, Pierfranco; Medas, Daniela; Parrini, Pierluigi
Graphical abstract: Highlights: Pinus nigra barks are good biomonitoring substrata for airborne Hg. Tree bark concentration for Hg may be influenced by sampling methodology. Sampling can be conveniently done at 150 cm height from the soil on the outer 1.5 cm. Sampling orientation with respect to wind directions does not affect Hg in barks. Negligible Hg is lost from bark tissues during leaching tests. Abstract: Tree barks are increasingly used as biomonitors of airborne pollutants. However, many authors stress the poor comparability of the results achieved in different studies. This drawback is mainly caused by a poor understanding of the critical sampling parameters to be considered. To minimize the biases that could be introduced during sampling, in this study the barks of Pinus nigra J.F. Arnold from thirteen sites were investigated in the abandoned Mt. Amiata mercury (Hg) mining district (Southern Tuscany, Italy) and surroundings. The influence of some sampling and analyzing parameters on Hg content was critically assessed. At each site, a total of eight bark samples were taken from a single tree at two heights (70 cm and 150 cm from soil) and at four different sides of the trunk, corresponding to the four cardinal directions; a composite soil sample was also collected. Mercury contents in barks range from 0.1 to 28.8 mg/kg, and are correlated with soil Hg contents (1–480 mg/kg), indicating that barks record both gaseous Hg concentrations in air, and wind-transported Hg-bearing particulate. For each tree, samples at 70 cm and 150 cm show Hg contents of the same order of magnitude, even if values for 150 cm are slightly less dispersed, possibly because barks at 70 cm are more influenced by random soil particles. There is no statistically significant dependence of Hg content on direction and tree age. Simulated rain events cause a negligible loss of Hg from barks. Results suggest that a convenient sampling practice for Pinus nigra is to collect a bark slice (typically 1–2 mm) within the outermost 1.5 cm layer.